2019
DOI: 10.1021/acsami.9b18891
|View full text |Cite
|
Sign up to set email alerts
|

Light-Activated Peptide-Based Materials for Sutureless Wound Closure

Abstract: Using chemically modified extracellular matrix proteins, such as collagen, in combination with light for tissue bonding reduces inflammation and minimizes scarring. However, full length animal or recombinant human collagen proteins are difficult to isolate/produce. Thus, short biomimetic collagen peptides with properties equivalent to collagen at both structural and functional levels may be ideal building blocks for the development of remotely triggered adhesives and fillers. In this work, the conjugation of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…[ 1–3 ] Therefore, effective and timely management of skin wounds remains challenging, especially for extensive or chronic wounds, often requiring additional interventions to promote healing. [ 4–6 ] A common modality currently clinically used to treat skin wounds is to reattach the injured tissue with medical sutures or staples, but it can only protect wounds from external damage and absorb tissue fluid [ 7,8 ] without an obvious therapeutic effect on the inflammation and proliferation stages of wound healing. Hence, designing novel functional wound dressing materials that can resolve the present problems is of the utmost importance in modern medical technology.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–3 ] Therefore, effective and timely management of skin wounds remains challenging, especially for extensive or chronic wounds, often requiring additional interventions to promote healing. [ 4–6 ] A common modality currently clinically used to treat skin wounds is to reattach the injured tissue with medical sutures or staples, but it can only protect wounds from external damage and absorb tissue fluid [ 7,8 ] without an obvious therapeutic effect on the inflammation and proliferation stages of wound healing. Hence, designing novel functional wound dressing materials that can resolve the present problems is of the utmost importance in modern medical technology.…”
Section: Introductionmentioning
confidence: 99%
“…Biophysical and computational approaches have shown that RB has a binding preference for positive regions of CLPs both to fibers in solution and hydrogel matrices [17,19]. For instances, although CLPI does not present a specific binding site for RB, the formation of an initial binary ground-state complex between RB and one CLP fiber was shown to be driven by electrostatic interactions [20,21]. The main electrostatic interactions are established between the phenolate and carboxylate groups of RB with side chains of lysine (Lys) residues present in CLPI [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…For instances, although CLPI does not present a specific binding site for RB, the formation of an initial binary ground-state complex between RB and one CLP fiber was shown to be driven by electrostatic interactions [20,21]. The main electrostatic interactions are established between the phenolate and carboxylate groups of RB with side chains of lysine (Lys) residues present in CLPI [20,21]. This initial binary ground-state complex represents a crucial step for the effective covalent crosslinking process of CLPI in the presence of RB.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation